Analysis of Raw Material Inventory Control Using The Economic Order Quantity Method at Geulis Bakery Store in Gunungsitoli City - Saota, Imelda Wulansari; Kakisina, Sophia Molinda; Hulu, Perlindungan Faebuadodo; Harefa, Idarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The study investigates the application of the Economic Order Quantity (EOQ) method in managing raw material inventory at Geulis Bakery Store in Gunungsitoli City. Utilizing a quantitative descriptive approach, the study aims to provide insights into inventory management practices, particularly focusing on the EOQ method's effectiveness. Data were collected through interviews, observation, and document analysis, with the research population consisting of raw material inventories at the bakery. Findings revealed that the EOQ method led to smaller but more cost-effective raw material orders compared to the previous ordering policy. Moreover, the EOQ method enabled the optimization of safety stock levels, reducing the risk of stockouts while minimizing inventory holding costs. The study highlights the enhanced efficiency achieved in inventory control through the EOQ method, emphasizing its potential to streamline operations and improve financial performance for small-scale enterprises like Geulis Bakery Store. Future research could explore the EOQ method's applicability in different industry contexts and evaluate its comparative effectiveness against other inventory management techniques. Overall, the study underscores the significance of adopting efficient inventory control strategies to enhance business competitiveness and sustainability in today's dynamic market environment.